Breast Cancer Treatment Practices in Elderly Women in a Community Hospital. (17th November 2011) - Wang, Hua; Singh, Awinder P.; Luce, Serena A. St.; Go, Alan R.
Abstract : Background . Elderly women with breast cancer are considered underdiagnosed and undertreated, and this adversely affects their overall survival. Methods . A total of 393 female breast cancer patients aged 70 years and older, diagnosed within the years 1989–1999, were identified from the tumor registry of The Brooklyn Hospital Center. Comparisons between the 3 different subgroups 70–74, 75–79, and 80 years and older were made using the Pearson Chi Square test. Results . Lumpectomy was performed in 42% of all patients, while mastectomy was done in 46% of patients. Adjuvant therapy such as chemotherapy, radiation therapy, and hormonal therapy were done in 12%, 25%, and 38%, respectively. Forty-seven percent of patients with positive lymph nodes received chemotherapy. Eighty-six percent of patients who were estrogen receptor-positive received adjuvant hormonal therapy. Overall five-year survival was only 14% for the ≥80 age group, compared to that of 32% and 35% for the 70–74 and the 75–79 age groups, respectively. Conclusions . Surgery was performed in majority of these patients, about half received lumpectomy, the other half mastectomy. Adjuvant therapies were frequently excluded, with only hormonal therapy being the most commonly used. Overall five-year survival is significantly worse in patients ≥80 years with breast cancer.